Non-invasive testing for liver pathology in alpha-1 antitrypsin deficiency. Issue 1 (15th December 2020) - Abbas, Syed Hamza; Pickett, Elisha; Lomas, David A; Thorburn, Douglas; Gooptu, Bibek; Hurst, John R; Marshall, Aileen
Abstract : Background: Many patients with alpha-1 antitrypsin deficiency (A1ATD) receive care in respiratory clinics without access to specialist hepatology expertise. Liver disease can develop asymptomatically, and non-invasive markers of fibrosis may help identify patients who require definitive assessment with liver biopsy. We evaluated the utility of non-invasive markers of liver fibrosis in A1ATD to guide testing in settings without ready access to hepatology expertise. Methods: Patients attending the London A1ATD service undergo assessment using blood tests to calculate the 'APRI' and 'FIB-4' score, liver ultrasound and Fibroscan. Liver biopsy is offered to patients who have abnormal liver function tests with abnormal liver ultrasound and/or liver stiffness >6 kPa on Fibroscan. Liver biopsies were assessed for the presence of A1AT, steatosis, fibrosis and inflammation. Results: 75 patients with A1ATD had results for analysis, 56% were female, age 16–82 years. 75% of patients had Fibroscan <6 kPa, 19% had Fibroscan 6–7.9 kPa and 6%>8 kPa. There was a significant correlation between FIB-4 and Fibroscan (r=0.244, p=0.035). Fibroscan >6 kPa corresponded to a FIB-4 score of >1.26. However, FIB-4 >1.26 had poor sensitivity (47%), specificity (32%) and positive-predictive value (PPV; 36%) to identify Fibroscan >6 kPa. The negative-predictive value (NPV) was stronger at 81%. APRI data were similar. Twelve patients underwent liver biopsy, with 11 reports available for analysis. Six had FIB-4 scores<1.26 and five had Fibroscan of <6 kPa. A1AT was present in 64% of biopsies, steatosis in 82%, mild fibrosis in 36%, moderate fibrosis in 9% and severe fibrosis in 9%. Conclusion: A combination of liver ultrasound and non-invasive fibrosis tests can help identify patients with A1ATD liver injury. However, APRI and FIB-4 scores alone had poor sensitivity and specificity to justify use as an independent tool for liver pathology in A1ATD.